Perilaku Nasabah terhadap Adanya Layanan Anjungan Tunai Mandiri (ATM) di LPD Desa Adat Beraban, Kecamatan Kediri, Kabupaten Tabanan - PRADNYAYANTI, NI PUTU WULAN MANIKA; SUAMBA, I KETUT; SUSRUSA, KETUT BUDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Customer Behavior Against the Presence of Automated Teller Machines (ATM) at Local Credit Institution (LPD) of Beraban Village, Kediri District, Tabanan Regency Local Credit Institutions (LPD) are non-bank financial institutions organized by local governments and are autonomous and oriented towards strengthening the economic and socio-cultural life of indigenous peoples in Bali. Increasing profits and progress made in LPD make it always carry out the latest innovations in products to be marketed. Technological developments are becoming very global with regard to the efficiency and ability of banks to earn non-interest income in the future. One of the information technology innovations that play a very important role in the banking world is ATM services. With the ATM service in the LPD, it will certainly make it easier for people to make transactions. The existence of this ATM service, of course, has to look at how the community will behave towards the latest innovations from the LPD. Behaviors are specific actions directed at some target object. While the desire to behave is a proposition that connects itself with future actions. This study aims to analyze customer behavior towards the existence of ATM services in terms of three indicators, namely the level of customer knowledge, customer attitudes, and customer actions. The data used in this study are primary data and secondary data. Primary data collection was obtained directly by researchers through observation, interviews and filling out questionnaires submitted to customers at the Beraban Village LPD as many as 100 respondents with a stratified random sampling technique, namely respondents were grouped into three groups based on customer balances. The overall analysis carried out is for the variable knowledge either or know about ATM. For the variable of customer attitudes towards ATM. are in the good category, meaning that customers have a very good attitude towards the existence of ATM. In the action variable, the customer already has a very good action on the existence of an ATM. From the results of a thorough analysis obtained, it is stated that customer behavior regarding the emergence of new innovations created by LPD to assist customer transactions in the form of ATM is good, where customers use and receive many benefits from the available ATM.